Two Seals of the Ninth Century B. С. from Shadikanni on the Ḫabur - Unger, E.
1. The Royal Seal from Tarbaṣu — 2. The Cultic Seal from the Treasury of the Marduk Temple at Babylon — 3. Šadikanni (Arban) on the Ḫabûr — 4. The Fate of the Two Seals.